Adaptive Speed Control of PMSM Drive System Based a New Sliding-Mode Reaching Law - Junejo, Abdul Khalique; Xu, Wei; Mu, Chaoxu; Ismail, Moustafa Magdi; Liu, Yi (IEEE transactions on power electronics, 2020)
In order to enhance the speed control performance of the permanent magnet synchronous motor (PMSM) with internal and external disturbances, a new adaptive terminal sliding mode reaching law (ATSMRL) is proposed with continuous fast terminal sliding mode control (CFTSMC). Firstly, the ATSMRL is presented with the aim of reducing the input control efforts, which can dynamically adopt all positive aspects in terms of the finite time convergence, high tracking precision, and reduction of the chattering in the control input of the system. Secondly, an extended sliding mode disturbance observer (ESMDO) is designed to estimate the total disturbances of the system, and then the estimated disturbance has been brought for the feed-forward compensation technique, which would enhance the disturbance rejection ability of the system. Afterwards, the close loop stability is validated by the Lyapunov function. Finally the comprehensive numerical and experimental analyses have been carried out to demonstrate the superiority of the ATSMRL method than those of conventional exponential sliding mode reaching law (ESMRL) and terminal sliding mode reaching law (TSMRL).